2019
DOI: 10.1111/jcmm.14155
|View full text |Cite
|
Sign up to set email alerts
|

Follistatin‐like protein 1 (FSTL1) promotes chondrocyte expression of matrix metalloproteinase and inflammatory factors via the NF‐κB pathway

Abstract: Background The expression of follistatin‐like protein 1 (FSTL1) is closely associated with diseases of the musculoskeletal system. However, despite being a well characterized inflammatory mediator, the effects of FSTL1 on chondrocytes are not completely understood. In this study, we investigated the effects of FSTL1 on the expression of inflammatory and catabolic factors in rat chondrocytes. Methods Rat chondrocytes were treated directly with various concentrations of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…43 Besides, Hu et al declared that follistatin-like protein 1 elevated the levels of MMP-13, IL-1β, TNF-α and IL-6 by activating the NF-κB pathway in chondrocyte. 44 We found that Sal treatment markedly decreased the levels of MMP-13 and TNF-α. MMP-13 was an important regulator that maintained the metabolic balance of chondrocytes.…”
Section: Discussionmentioning
confidence: 66%
“…43 Besides, Hu et al declared that follistatin-like protein 1 elevated the levels of MMP-13, IL-1β, TNF-α and IL-6 by activating the NF-κB pathway in chondrocyte. 44 We found that Sal treatment markedly decreased the levels of MMP-13 and TNF-α. MMP-13 was an important regulator that maintained the metabolic balance of chondrocytes.…”
Section: Discussionmentioning
confidence: 66%
“…Studies have shown that FSTL1 can alleviate the occurrence of inflammatory pulmonary fibrosis, suggesting that FSTL1 may be closely related to the occurrence of inflammation [23]. Further studies have reported that FSTL-1 regulates the secretion of inflammatory factors such as interleukin-α, TNF-α, and ADAMTS and participates in the immune inflammatory response in tissues in many systemic autoimmune diseases, including systemic lupus erythematosus, ulcerative colitis, rheumatoid arthritis, and Sjogren's syndrome [24,25]. In rheumatoid arthritis and osteoarthritis, FSTL1 exacerbates inflammation by increasing the expression of inflammatory factors and promoting synovial proliferation by activating the NF-κB signaling pathway [25].…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published study (50), FSTL1 increased the expression of inflammatory cytokines (IL‐1β, TNFα, IL‐6) and metalloproteinases, including MMP13, in rat chondrocytes. The results of this work are in contradiction with our data.…”
Section: Discussionmentioning
confidence: 87%